A genomic and functional inventory of deubiquitinating enzymes. - Nijman, S; Luna-Vargas, M; Velds, A; Brummelkamp, T; Dirac, A; Sixma, T; Bernards, R (2005)
Posttranslational modification of proteins by the small molecule ubiquitin is a key regulatory event, and the enzymes catalyzing these modifications have been the focus of many studies. Deubiquitinating enzymes, which mediate the removal and processing of ubiquitin, may be functionally as important but are less well understood. Here, we present an inventory of the deubiquitinating enzymes encoded in the human genome. In addition, we review the literature concerning these enzymes, with particular emphasis on their function, specificity, and the regulation of their activity.